Non-covalent intramolecular interactions through ligand-design promoting efficient photoluminescence from transition metal complexes - Koshevoy, Igor O.; Krause, Maren; Klein, Axel (Coordination chemistry reviews, 2020)
Ligand design aimed at arranging ligand entities and functional groups in order to generate non-covalent interactions, steric strain and ligand entanglement allowing to tune the electronic properties of transition metal complexes such as triplet emission energy and quantum yields. [Display omitted] •Ligand design allows for turning-on of non-covalent intramolecular interactions.•H bridges, π-stacking, ligand entanglement and bulky groups promote rigidity.•Lewis acids, and bases further modify the electronic states.•Both effects allow tuning the electronic states and improve luminescence efficiency.•This review provides for the first time an overview of this approach. Ligand design allows arranging ligand entities and functional groups in order to generate a plethora of non-covalent interactions such as π stacking, H bridging, and Lewis acid-base interactions in the second coordination sphere of transition metal complexes and thus modulate the photophysical properties. In addition to these forces, steric strain and ligand entanglement can lead to massive restrictions in the molecular geometry of complexes and in consequence to high rigidity and thus high geometrical similarity of the complexes electronic ground and excited states. This similarity is one of the prerequisites for efficient photoluminescence of such complexes since it hampers the unwanted radiationless decay from the excited states. Compared with other strategies to design efficient triplet emitting complexes, the approach of intramolecular non-covalent interaction has only recently entered the stage and has thus a lot of potential. In this review we will trace this approach presenting illustrative and recent examples for suitable ligand design.